Cell surface glycoprotein of reactive stromal fibroblasts as a potential antibody target in human epithelial cancers. - Garin-Chesa, P (1990)
The F19 antigen is a cell surface glycoprotein (Mr, 95,000) of human sarcomas and proliferating, cultured fibroblasts that is absent from resting fibroblasts in normal adult tissues. Normal and malignant epithelial cells are also F19-. The present immunohistochemical study describes induction of F19 in the reactive mesenchyme of epithelial tumors. F19+ fibroblasts were found in primary and metastatic carcinomas, including colorectal (18 of 18 cases studied), breast (14/14), ovarian (21/21), bladder (9/10), and lung carcinomas (13/13). In contrast, the stroma of benign colorectal adenomas, fibrocystic disease and fibroadenomas of breast, benign prostate hyperplasia, in situ bladder carcinomas, and benign ovarian tumors showed no or only moderate numbers of F19+ fibroblasts. Analysis of dermal incision wounds revealed that F19 is strongly induced during scar formation. Comparison of F19 with the extracellular matrix protein tenascin, a putative marker of tumor mesenchyme, showed a cellular staining pattern for F19 vs. the extracellular matrix pattern for tenascin and widespread expression of tenascin in F19- normal tissues and benign tumors. Our results suggest that the F19+ phenotype correlates with specialized fibroblast functions in wound healing and malignant tumor growth. Because of its abundance in tumor mesenchyme, F19 may serve as a target for antibodies labeled with radioisotopes or toxic agents, or inflammatogenic antibodies, in carcinoma patients.